Rotator Cuff Injuries A Clinical Casebook (Springer International Publishing, 2018)
Comprised exclusively of clinical cases presenting injuries to and management of the rotator cuff, this concise, practical casebook will provide orthopedic surgeons with the best real-world strategies to properly manage the various kinds of cuff injury they may encounter. Each chapter is a case that opens with a unique clinical presentation, followed by a description of the diagnosis, assessment and management techniques used to treat it, as well as the case outcome, literature review and clinical pearls and pitfalls. Cases included illustrate different management strategies for rotator cuff surgery, including arthroscopic repair for tendonitis and tears, open and mini-open repair for severe tears, latissimus dorsi and pectoralis tendon transfer, arthroscopic debridement, hemiarthroplasty and total reverse arthroplasty, biological augmentation, and revision repair after retear and infection. Pragmatic and reader-friendly, Rotator Cuff Injuries: A Clinic al Casebook is an excellent resource for orthopedic surgeons and sports medicine specialists confronted with both common and complex injuries to the rotator cuff.